2001
DOI: 10.1590/s0100-41582001000200019
|View full text |Cite
|
Sign up to set email alerts
|

Differences in competitive ability among races of Colletotrichum graminicola in mixtures

Abstract: Mixtures of races of Colletotrichum graminicola, causing sorghum (Sorghum bicolor) anthracnose and differing in their virulence range, were inoculated for five and six generations on the susceptible sorghum cultivar BR009 (Tx623), in two experiments in a greenhouse. In each generation a sample of 50 single spore isolates was obtained and inoculated on a standard differential set to determine the proportion of each race in the mixture. Isolates of the race 30A, with the narrowest virulence range, predominated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 9 publications
2
15
0
1
Order By: Relevance
“…Competition between breeds may also reflect a greater or lesser proportion of complex breeds in the pathogen population. Casela et al (2001) demonstrated the difference in competitive hability between breeds of C. sublineolum with different degrees of complexity.…”
Section: Correlationmentioning
confidence: 95%
See 1 more Smart Citation
“…Competition between breeds may also reflect a greater or lesser proportion of complex breeds in the pathogen population. Casela et al (2001) demonstrated the difference in competitive hability between breeds of C. sublineolum with different degrees of complexity.…”
Section: Correlationmentioning
confidence: 95%
“…This diversification can be performed through the use of multilines or mixtures of varieties in the form of non-isogenic lines (Wolfe, 1985; Lannou & Mundt, 1996). Multilines and mixtures are based on the occurrence of the confrontation of the pathogen with a broad diversity of resistance genes in the host (Parlevliet, 1993;Casela et al, 2001), leading to a reduction in the severity of the disease and a broadening of variability in the pathogen. Guimarães et al (1998) and Costa et al (2005) analyzed this process in the Sorghum bicolor/Colletotrichum sublineolum pathosystem and assessed the efficiency of sorghum mixtures in controlling anthracnose in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…The inoculations were performed 30 days after plant Table 1 Sequence of sorghum hybrids in rotation system for seven planting seasons. emergence with 500 ml of conidial suspension sprayed with a hand-sprayer (Casela et al, 1998(Casela et al, , 2001. Twelve days after inoculation, the modified Cardwel scale (Cardwel et al, 1989), with notes ranging from 1 to 5, was used to evaluate the disease severity, where: 1 e presence of chlorotic flecks; 2 e small red spots in the leaf lamina; 3 e necrotic lesions, sometimes elongated, but no acervuli formed; 3.1 to 3.9 e necrotic lesions varying in size and amount and with little sporulation; 4 e necrotic lesions formed with acervuli present in the center; 5 e necrotic lesions, sometimes coalescing with abundant sporulation.…”
Section: Methodsmentioning
confidence: 99%
“…In Brazil, the breakdown of resistance to anthracnose in the grain sorghum BR 304 is likely associated with the expansion of the planted area and its use by seed companies over a long period. This fact indicates the need for a continuous monitoring of local pathogen populations (Casela et al, 1997(Casela et al, , 2001Silva et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…C. sublineolum has a high level of variability and this variability results in the fast adaptation of the pathogen to the resistant cultivars in use, breaking their resistance very quickly (Singh et al, 2006;Moore et al, 2008;Silva et al, 2008). The use of multilines or mixtures of varieties in the form of non-isogenic lines seemed to be effective in reducing the disease severity (Casela et al, 2001b). Guimaraes et al (1998) and Costa et al (2005) analysed this process in the Sorghum bicolor/C.…”
Section: Host Plant Resistancementioning
confidence: 99%